1998
DOI: 10.1183/09031936.98.12051113
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of expiratory tidal flow patterns as a diagnostic tool in airflow obstruction

Abstract: In 1981, we made the observation that tidal flow versus time has a distinctive pattern in patients with airflow obstruction that is different from the sinusoidal appearance seen in normal subjects. To quantify this difference, we described timing indices derived from the analysis of tidal expiratory flow [1]. These indices, volume expired when the peak tidal expiratory flow reached (VPTEF)/tidal volume (VT) and (time to peak expiratory tidal flow (tPTEF)/ expiratory time (tE) closely correlated with each other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 26 publications
2
54
0
Order By: Relevance
“…On the other hand, assessment of the spontaneous expiratory flow-volume (SEFV) curve has been reported as a method to evaluate the severity of airway obstruction, which has the advantage that it is easily measured via spirometry during quiet breathing. [3][4][5][6][7][8][9][10] Shortening of the time to reach the peak expiratory flow 3 and the slope of the late SEFV curve, 4 which can be obtained from the SEFV curve, has been reported to be related to airway obstruction. Moreover, a method to assess the pattern of the SEFV curve has been reported, and concavity of the SEFV curve has been found to be related to expiratory flow limitation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, assessment of the spontaneous expiratory flow-volume (SEFV) curve has been reported as a method to evaluate the severity of airway obstruction, which has the advantage that it is easily measured via spirometry during quiet breathing. [3][4][5][6][7][8][9][10] Shortening of the time to reach the peak expiratory flow 3 and the slope of the late SEFV curve, 4 which can be obtained from the SEFV curve, has been reported to be related to airway obstruction. Moreover, a method to assess the pattern of the SEFV curve has been reported, and concavity of the SEFV curve has been found to be related to expiratory flow limitation.…”
Section: Introductionmentioning
confidence: 99%
“…The results of MORRIS et al [1] and WILLIAMS et al [2] are, therefore, interesting from a clinical perspective be-cause they suggest that the severity of airflow obstruction, a parameter of key concern to the respiratory specialist, may be derived easily and noninvasively, namely from airflow measurements at the mouth. The physiological basis of this approach is not difficult to appreciate.…”
Section: Jht Batesmentioning
confidence: 99%
“…The two papers in this issue from the Osler Chest Unit at Oxford University [1,2] exploit the fact that the breathing pattern in humans is affected in characteristic ways when the pulmonary airways are obstructed. MORRIS et al [1] examined the latter part of the tidal expiratory flow pattern in patients with varying degrees of airflow obstruction and found that the expiratory time constant correlated positively with standard measures of airflow obstruction.…”
Section: Jht Batesmentioning
confidence: 99%
See 2 more Smart Citations